2010
DOI: 10.1097/prs.0b013e3181e09533
|View full text |Cite
|
Sign up to set email alerts
|

Management of Isolated Sagittal Synostosis in the Absence of Scaphocephaly: A Series of Eight Cases

Abstract: It is unclear why the secondary features of sagittal synostosis did not develop in these cases. Possible explanations include fusion of the suture late after the majority of skull growth has taken place and a patent metopic suture allowing growth to occur anteriorly; other sutures appeared patent radiologically but may not have been functioning normally. Although difficult to recognize, patients with isolated sagittal synostosis in the absence of scaphocephaly are important to identify because they are at high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 10 publications
1
31
0
Order By: Relevance
“…Our use of a threshold of more than 15 mm Hg to define an abnormally elevated ICP is consistent with that used by all previous studies that have undertaken overnight intracranial ICP monitoring in craniosynostosis, no matter whether an extradural or subdural device was employed. 6,11,13,28,35,42,43,45,46 The pathological significance of multiple B-type waves is also well recognized in the literature. 11,35,50 Consistent with the patient series of van Veelan et al and Cetas et al, we found that elevated ICP was diagnosed late, at least 2 years after primary surgery, with a mean at just under 4.5 years of follow-up.…”
Section: Discussionmentioning
confidence: 96%
“…Our use of a threshold of more than 15 mm Hg to define an abnormally elevated ICP is consistent with that used by all previous studies that have undertaken overnight intracranial ICP monitoring in craniosynostosis, no matter whether an extradural or subdural device was employed. 6,11,13,28,35,42,43,45,46 The pathological significance of multiple B-type waves is also well recognized in the literature. 11,35,50 Consistent with the patient series of van Veelan et al and Cetas et al, we found that elevated ICP was diagnosed late, at least 2 years after primary surgery, with a mean at just under 4.5 years of follow-up.…”
Section: Discussionmentioning
confidence: 96%
“…The incidence of raised ICP in these patients has not been previously reported in the literature, although a recent study conducted by our unit in 6 nonscaphocephalic SC patients who underwent ICP monitoring showed that 4 (67%) had elevated ICP. 36 This high rate may reflect an underlying increased risk of raised ICP in mild or nonscaphocephalic patients compared with the SC population as a whole. Alternately, it may be a function of the patients' age (mean 46 months), given that Renier et al 41 previously found a correlated increase in ICP with age, up to 6 years of age, in craniosynostosis.…”
mentioning
confidence: 99%
“…In contrast, non-scaphocephalic sagittal synostosis is a rare diagnosis. Morritt et al [10] were the first to report non-scaphocephalic sagittal synostosis in 8 (4.1%) of the total 193 patients who had isolated sagittal synostosis. According to the report, there are a number of possible explanations including the following: if fusion of the suture occurred at a later stage after the majority of skull growth had taken place, then, the secondary defect induced by compensatory over-growth of adjacent sutures is likely to be less severe in comparison to the secondary defect arising from fusion that occurred at an earlier stage.…”
Section: Discussionmentioning
confidence: 99%